Human-Induced Impacts on Land Surface Temperature Dynamics in Osogbo, Osun State, Nigeria - Simon, Ajih, Enenche; Olutayo, Balogun, Bolarinwa; Onu, Ekwe, David (European Scientific Journal, ESJ, 2020)
The main goal of this study is to evaluate the impacts of humaninduced activities on land surface temperature dynamics of Osogbo, in Osun State, Nigeria. Land surface temperature dynamics, land use land cover dynamics and the relationship between land surface temperature (LST) and land-use land-cover (LULC) were assessed using Landsat satellite data (ETM+ and OLI/TIRS) of Oshogbo, Osun State, Nigeria. The radiometrically corrected thermal infrared bands of the Landsat images of 2000 and 2018 were used to retrieve land surface temperature while the Maximum Likelihood algorithm in Erdas imagine 9.2 was used to generate a classified image for the two periods. Land surface temperature maps, land cover index maps and Normalized Differential Vegetation Index (NDVI)) were generated. Correlation analysis using Pearson’s Product Moment Method was carried out between land surface temperature and normalized differential vegetation index (NDVI) data and the land cover index was digitized and overlaid on the LST map of 2018 to determine the association between them. The results revealed noticeable decrease in vegetated areas of Osogbo with an accompanying increase in land surface temperature from 28.045°C in 2000 to 29.200°C in 2018. Built-up increased within the same periods from 19 to 42%, which could be attributed to anthropogenic activities. The land surface temperature distribution maps showed a more pronounced intensity in areas of significant human activities than in areas covered by vegetation and waterbody. The correlation coefficient values of –0.54418 and -0.48513 observed in the land surface temperature and normalized differential vegetation index values for 2000 and 2018 respectively, indicated an inverse relationship between the two variables. The study concluded that the nature of land use / land cover patterns in Osogbo have impacted its land surface with a corresponding increase in land surface temperature. It is expected that as the city expands further, the magnitude of the land surface temperature will also increase thereby affecting the living conditions of the urban populace.